Application of NIR Spectral Absorbance Linearization and Gradient Shift in Quantifying Aqueous Glucose and Fructose Solution - Fairuz Omar, Ahmad; Atan, Hanafi; Zubir MatJafri, Mohd (Asian Journal of Chemistry, 2011)
Spectral data analysis is an essential companion to spectroscopic experiment. The purpose is to produce a reliable data representation on examined samples, which in this research is on quantification of biochemical composition. Many different analyses have been introduced and performed regularly in spectroscopy measurement such as derivatives, principal component analysis, partial least square-discrimination analysis, normalization and linear regression. While in the other hand, innovative approach has been continuously introduced with improved solutions to current techniques. This paper introduced NIR spectral absorbance linearization and gradient shift in quantifying two aqueous monosaccharide solutions, namely glucose and fructose. In this paper, spectral absorbance linearization and gradient shift has manage to provide a better coefficient of determination, R2 in quantifying glucose and fructose concentration (in unit of Brix) if compared to single wavelength analysis.